Justiça juvenil e o Sistema Interamericano de Direitos Humanos: a experiência brasileira - Gonçalves, Eduardo Moureira (2024)
The present work aims to study the Brazilian Juvenile Justice in light of the Regional Human Rights Protection System, with an emphasis on the actions of the Inter-American Court of Human Rights and the key cases in the Americas involving adolescents in conflict with the law. This will be achieved through the analysis of common practices among the members of the Organization of American States (OAS) and how these practices can impact the Brazilian legal framework. Thus, the general objective of the dissertation is to analyze the Brazilian model of protection for adolescents in conflict with legal norms and to examine the emblematic decisions issued by the Inter-American Court. The research includes a detailed investigation of the Tatuapé case from FEBEM versus Brazil, with a specific focus on understanding the significant contributions this case made to the advancement of the Socio-Educational System in Brazil. The discussion also encompasses relevant aspects concerning the age of criminal responsibility and the various schools of thought on Juvenile Justice, allowing for a critical reflection on the subject. In this context, the study seeks to understand how the integration of human rights and Juvenile Justice can promote more appropriate and humane care for adolescents, facilitating their social reintegration. The analysis of the decisions of the Inter-American Court is crucial for identifying precedents that may guide public policies and justice practices aimed at this vulnerable population. Among the aspects addressed, the research will examine international guidelines for the protection of adolescents' rights and how these can be incorporated into Brazilian legislation, offering a pathway for the transformation of the Socio-Educational System. Furthermore, the study investigates the consequences of injustices and illegalities committed against adolescents, reflecting on the need for a more attentive approach from competent authorities in promoting the human rights of this age group. Through this research, the aim is to contribute to the debate on establishing a model of Juvenile Justice that not only respects the rights of adolescents but also fosters their dignity and full exercise of citizenship. The dynamic relationship between international standards, the decisions of the Inter-American Court, and the nuances of the national system can serve as a guide for future legislative reforms and judicial practices in Brazil